(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction:An unexplained pleural effusion is a difficult diagnostic dilemma that needs further histological study for a definitive etiological diagnosis. Video assisted thoracoscopic (VATS) pleural biopsy is a minimally invasive procedure that could resolve this problem. The study is conducted to determine the efficacy of VATS pleural biopsy in the diagnosis of unexplained pleural effusion. Methods: This cross-sectional study was to investigate our experience of VATS pleural biopsy for unexplained pleural effusion which was conducted at our center. All patients who underwent VATS pleural biopsy for unexplained pleural effusion during the period of January 2019 to December 2019 were included in the study. Epidemiological, clinical, radiological & histopathological data of the patients were collected and analyzed Results: The overall diagnostic yield of VATS pleural biopsy in our study was 95%. Malignancy was the most common histological diagnosis for unexplained pleural effusion followed by tuberculosis. In patients with malignant effusion, metastatic adenocarcinoma was commonly observed finding followed by metastatic squamous cell carcinoma. Minor complications related to the procedure were noticed with no mortality. Conclusion: VATS pleural biopsy has high definitive diagnostic accuracy in the evaluation of unexplained pleural effusions. J Bangladesh Coll Phys Surg 2023; 41: 141-149